Implementation of Democratic Leadership Style and Transformational Head of Madrasah in Improving The Quality - Aulia Diana Devi; Subiyantoro Subiyantoro (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2021)
The management of educational institutions or organizations is a very important issue in the world of education. Because the success of an educational institution depends on the leadership of the head of the madrasah. This research aims to find out the implementation of democratic leadership style and transformational head of Madrasah in MAN 1 Tulang Bawang Barat Lampung province. The method used is a descriptive analysis using a qualitative approach. This study uses primary data sources obtained through interviews and secondary data sources obtained through online media. The results showed that the ability of the principal to implement the vision and mission in improving the quality of education in MAN 1 Tulang Bawang Barat can be seen from the behavior of the principal in carrying out the preparation of the school's vision and mission with a joint discussion, the creation of an education program guided by the quality standards of education, and promoting civility, as well as mobilizing school residents to participate in improving the quality of education. The ability of the principal to communicate effectively in improving the quality of education in MAN 1 Tulang Bawang Barat is reflected in the principal's behavior in cultivating a disciplined lifestyle and interacting directly with school residents and in problem-solving through a system of discussions, meetings, or deliberations. then, the ability of the principal in developing academic and non-academic programs that can produce good quality for the school.